The Moral Values of the Main Characters in “Sea Beast” Film - Hadmoko, Wahyu; Suwandi; Lestari, Siti (Melati Institute, 2025)
Hadmoko Wahayu. 2025. Universitas PGRI Semarang, English Language Education Study Program, Faculty of Language and Arts Education, “The Moral Values of the Main Characters in the film 'Sea Beast' 2022 Final Thesis” Prof. Dr. Suwandi, M.Pd. as the first advisor and Dra. Siti Lestari, M.Pd. as the second advisor. This final thesis aims to analyze the moral values contained in the film “Sea Beast” 2022, particularly the main characters. This research employs a descriptive qualitative method. By using descriptive qualitative methods, this research describes the characters in the film “The Sea Beast” (2022) in great detail and methodically; more specifically, the researcher aims to explain and depict the changes in the personality of the characters, especially the main characters, and the factors influencing them. The main objectives of this research are: (1) To examine the various moral standards present in the film “The Sea Beast.” (2) To determine which positive moral principles dominate the film “The Sea Beast.” (3) To reveal the dominant positive moral values in the film “The Sea Beast” that can contribute to the English learning process, particularly in character development of students through film media. This research examines various moral ideals found in the film “The Sea Beast” using the theory of Linda and Eyre (1993). The values of being and giving are two categories of moral values identified by Linda and Eyre (1993). The category falls into one of the twelve categories of moral principles. The researchers also found that courage is the dominant moral value in the film. There are also positive moral values that can contribute to the process of learning English.